2023
DOI: 10.3390/biom13030490
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in Health and Disease: A Perspective for Livestock Production

Abstract: Mounting evidence in the literature indicates an important role of endogenous and exogenous melatonin in driving physiological and molecular adaptations in livestock. Melatonin has been extensively studied in seasonally polyestrous animals whereby supplementation studies have been used to adjust circannual rhythms in herds of animals under abnormal photoperiodic conditions. Livestock undergo multiple metabolic and physiological adaptation processes throughout their production cycle which can result in decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 113 publications
1
3
0
Order By: Relevance
“…It has been demonstrated that melatonin is involved in a bidirectional circuit with the immune system [6] acting as an "immunological buffer" accompanied by innate and other specific responses of the immune system. Particularly, melatonin contributes to improvement of the immune response via two main mechanisms; it amplifies antigen presentation to immunocompetent cells, enhancing the antibody response, and it modulates cytokine production resulting in controlling cellular responses [24]. Accordingly, in the present study, KM-ewes registered the higher level of IgG, both in blood and colostrum samples, compared to other groups.…”
Section: Discussionsupporting
confidence: 49%
“…It has been demonstrated that melatonin is involved in a bidirectional circuit with the immune system [6] acting as an "immunological buffer" accompanied by innate and other specific responses of the immune system. Particularly, melatonin contributes to improvement of the immune response via two main mechanisms; it amplifies antigen presentation to immunocompetent cells, enhancing the antibody response, and it modulates cytokine production resulting in controlling cellular responses [24]. Accordingly, in the present study, KM-ewes registered the higher level of IgG, both in blood and colostrum samples, compared to other groups.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, studies have shown that melatonin plays a bidirectional role in the immune system, acting as a buffer to regulate innate and other specific immune responses [17]. Melatonin enhances immune functions through two main mechanisms: increasing antigen presentation to immune cells, thereby boosting antibody production, and regulating cytokine production to control cellular responses [18]. Specifically, melatonin administration enhances cytokine production by increasing the proliferation of B cells and the release of cytokines associated with the T helper cells type 1 (Th1) immune response, such as interleukin (IL)-2 and interferongamma (IFN-γ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence shows that melatonin has considerable potential for optimizing animal physiological functions and, in turn, improving the efficiency of animal husbandry (Li et al 2023;Contreras-Correa et al, 2023).…”
Section: Introductionmentioning
confidence: 99%